15‐Epi‐Lxa 4 and MaR1 counter inflammation in stromal cells from patients with Achilles tendinopathy and rupture. Issue 7 (27th March 2019) - Dakin, Stephanie G.; Colas, Romain A.; Newton, Julia; Gwilym, Stephen; Jones, Natasha; Reid, Hamish A. B.; Wood, Simon; Appleton, Louise; Wheway, Kim; Watkins, Bridget; Dalli, Jesmond; Carr, Andrew J.
ABSTRACT: Resolution of inflammation is poorly understood in Achilles tendon disorders. Herein, we investigated the bioactive lipid mediator profiles of tendon‐derived stromal cells isolated from patients with Achilles tendinopathy (AT) or Achilles rupture (AR) under baseline and IL‐1β–stimulated conditions. We also determined whether incubating these cells with 2 of the mediators produced by tendon‐derived stromal cells, 15‐epi‐Lipoxin A4 (15‐epi‐LXA4 ) or maresin (MaR)‐1, moderated their proinflammatory phenotype. Under baseline conditions, AT cells showed concurrent increased levels of proinflammatory eicosanoids and proresolving mediators compared with AR cells. IL‐1β treatment induced profound prostaglandin E2 release in AR compared with AT cells. Incubation of IL‐1β treated AT and AR tendon‐derived stromal cells in 15‐epi‐LXA4 or MaR1 reduced proinflammatory eicosanoids and potentiated the release of proresolving mediators. These mediators also induced specialized proresolving mediator (SPM) biosynthetic enzymes arachidonate lipoxygenase (ALOX) 12 and ALOX15 and up‐regulated the proresolving receptor ALX compared with vehicle‐treated cells. Incubation in 15‐epi‐LXA4 or MaR1 also moderated the proinflammatory phenotype of AT and AR cells, regulating podoplanin, CD90, signal transducer and activator of transcription (STAT)‐1, IL‐6, IFN regulatory factor (IRF) 5, and TLR4 and suppressed c‐Jun N‐terminal kinase 1/2/3, Lyn, STAT‐3, and STAT‐6 Phosphokinase signaling. In summary, we identify proresolving mediators that are active in AT and AR and propose SPMs, including 15‐epi‐LXA4 or MaR1, as a potential strategy to counterregulate inflammatory processes in these cells.—Dakin, S. G., Colas, R. A., Newton, J., Gwilym, S., Jones, N., Reid, H. A. B., Wood, S., Appleton, L., Wheway, K., Watkins, B., Dalli, J., Carr, A. J. 15‐Epi‐LXA4 and MaR1 counter inflammation in stromal cells from patients with Achilles tendinopathy and rupture. FASEB J. 33, 8043–8054 (2019). www.fasebj.org